2021
DOI: 10.21203/rs.3.rs-116850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic depletion of subcellular NAD pools reveals their interconnectivity and a buffering function of mitochondria

Abstract: The coenzyme NAD is consumed by signaling enzymes including poly-ADP-ribose-polymerases (PARPs) and sirtuins. Understanding the mechanisms of aging-associated NAD decline and how cells cope with decreased NAD concentrations requires model systems reflecting chronic NAD deficiency. To evoke compartment-specific over-consumption of NAD, we have engineered cell lines expressing PARP activity in mitochondria, the cytosol, endoplasmic reticulum, or peroxisomes. Irrespective of the compartment targeted, total cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 89 publications
(138 reference statements)
2
7
0
Order By: Relevance
“…To date, the cytosolic, nuclear, and mitochondrial NAD + pools have been best described. Using the PARAPLAY assay, which is based on expression of the catalytic domain of poly-ADP-ribosyltransferase 1 (PARP1) in various subcellular compartments [28], pools of NAD + in peroxisomes, ER, and Golgi complex [29,30] were demonstrated. It was shown that NAD + is transported into peroxisomes using the mitochondrial type carrier SLC25A17 [13].…”
Section: Human Nad + Biosynthesis and Its Compartmentationmentioning
confidence: 99%
“…To date, the cytosolic, nuclear, and mitochondrial NAD + pools have been best described. Using the PARAPLAY assay, which is based on expression of the catalytic domain of poly-ADP-ribosyltransferase 1 (PARP1) in various subcellular compartments [28], pools of NAD + in peroxisomes, ER, and Golgi complex [29,30] were demonstrated. It was shown that NAD + is transported into peroxisomes using the mitochondrial type carrier SLC25A17 [13].…”
Section: Human Nad + Biosynthesis and Its Compartmentationmentioning
confidence: 99%
“…The free NAD concentration has been measured to be approximately 230 μM in the mitochondria and 110 μM in the cytosol of parental HEK293 cells [52], whereas the 293mitoPARP cell line displays an up to 40-50% decrease in cellular NAD [41] and a severe depletion of NAD in mitochondria with only 10-20% of the mitochondrial NAD remaining [41] compared to parental HEK293 cells. The free NAD concentration in 293mitoPARP was thus decreased to approximately 66 μM in the cytosol and 23 μM in the mitochondria [41]. To model the changes related to free NAD concentrations, we retrieved 𝐾 𝑚 values from the Brenda [49] enzyme database and adjusted the flux boundaries (cf.…”
Section: Resultsmentioning
confidence: 99%
“…A cell line expressing PARP1 targeted to mitochondria has been used [40][41][42][43]. Proteins and peptides were quantified by VanLinden et al [41] via an MS/MS-based approach using tandem mass tags [44].…”
Section: Proteomics Datamentioning
confidence: 99%
See 2 more Smart Citations